XRD and 29Si MAS NMR study on carbonated cement paste under accelerated carbonation using different concentration of CO2. (June 2019) - Liu, Wei; Li, Yong-Qiang; Tang, Lu-Ping; Dong, Zhi-Jun
Graphical abstract: In the carbonation chamber, a designated concentration of CO2 was achieved by mixing pure CO2 gas with fresh air. An electronic sensor, sensitive to CO2 with a precision of 0.01%, was put inside the chamber to measure the concentration of carbon dioxide. Abstract: In this study, the chemical composition of cement pastes, exposed to accelerated carbonation using different concentration of CO2 (3%, 10%, 20%, 50%, 100%), have been determined and compared with those of natural carbonation (0.03%). Quantitative X-ray diffraction (QXRD) and 29 Si Magic Angle Spinning Nuclear Magnetic Resonance (MAS NMR) were used for characterisation and quantitative analysis of the carbonated phases. The obtained QXRD results revealed that the complete carbonation was hardly attained. Calcite, aragonite and vaterite were in co-existence after accelerated carbonation, while vaterite was dominant. The preferential polymorphic precipitation of the three crystal forms of calcium carbonate was affected by the carbonation degree of C-S-H and the duration of the carbonation process, but not by the concentration of CO2 . The NMR results indicated that C-S-H gel was strongly decalcified, and calcium modified silica gel was formed after carbonation. The C-S-H decalcification, under all the accelerated carbonation conditions, was clearly more pronounced than that under the natural carbonation conditions. When the concentration of CO2 was in the range of 3%–20%, the ratio of decalcified to remaining C-S-H was similar, in a range of 5–6, while under the higher concentration of CO2 this ratio was increased to >8. Therefore, in consideration of both acceleration rate and measurement uncertainty, the higher concentration, up to 20%, of CO2 in an accelerated carbonation should be applicable.